Egy ezeréves házasság felbontása: Turócszentmárton 1918. október 31. - Popély, Gyula (Acta Scientiarum Socialium, 2018)
The birth of the Czechoslovakian state during the autumn of 1918 was related to several symbolic events and several, geographically distant locations. Such locations were Prague, Paris, Pittsburgh and Turócszentmárton. In the latter town, the Slovakian nation broke up their millennium-long marriage with the Hungarian state and solemnly announced that they wish to live within the forming Czechoslovakian state. Our paper presents the details on what happened in Turócszentmárton on October 30, and the morning after, following Milan Hodza’s arrival.